A new Antarctic heterobranch clade is sister to all other Cephalaspidea (Mollusca: Gastropoda). (27th July 2016) - Moles, Juan; Wägele, Heike; Schrödl, Michael; Avila, Conxita
Abstract : For a long time, Diaphanidae has been considered a basal family within Cephalaspidea, based on the presence of plesiomorphic morphological features within this taxon. Traditionally, the family contained the genera Bogasonia, Colobocephalus, Colpodaspis, Diaphana, Newnesia, Toledonia and Woodbridgea . Some phylogenetic analyses of several of these genera support the basal position of Diaphanidae within Cephalaspidea sensu stricto . However, the family is presently confirmed to be a polyphyletic taxon in which only the genus Diaphana is included. Several genera previously embraced within the family, such as the monotypic Newnesia, have never been previously analysed in molecular studies. Here, we provide an extensive morphological, anatomical and histological description of a new species of Newnesia from Antarctic deep waters (967–1227 m depth) in the Drake Passage. We also discuss the similarities to the traditional Diaphanidae genera to try to shed light into this phylogenetic conundrum. We sequenced cytochrome c oxidase subunit I, 16S rRNA, 28S rRNA and histone H3 markers of Newnesia antarctica and Newnesia joani n. sp. We analysed a comprehensive dataset of sequenced genera to evaluate the placement of both Newnesia species within the cephalaspidean families. Maximum‐likelihood and Bayesian phylograms support the monophyly of N. joani n. sp. and suggest cryptic speciation in N. antarctica specimens. Newnesia is recovered as the most basal offshoot of Cephalaspidea, suggesting the establishment of a new family restricted to Antarctic waters, named Newnesiidae n. fam., to hold both species. The possible Antarctic origin of Cephalaspidea is discussed.